Internationalization Process of Thai Multinational Case of Charoen Pokphand Group(CP Group) - Abbas Paliket (2009)
The study of multinational corporations (MNCs) has been a fundamental component of the international business literature. Most studies have focused on the international expansion of MNCs from the western and very little academic attention examines and analyses the internationalization strategies and characteristics of Asian MNCs. This study explored the internationalization process of MNC from Thailand, namely Charoen Pokphand Group (CP Group), a leading agri-business company in the country. Its motives, foreign market selection and foreign market entry strategy chosen in setting up its operations abroad are deeply analyzed. This study discovered that internationalization process of Thai firm through post and pre crisis, where the pre-crisis international expansion relied more on networking capabilities rather than industry-specific technological skill, while the post-crisis adjustments of Thai multinationals displayed a different strategy that placed much more emphasize on strengthening their industry-specific technological capabilities.